ChemInform Abstract: Asymmetric Synthesis of (—)‐Bissetone via a Highly Enantioselective Hetero‐Diels—Alder Reaction. Issue 4 (28th January 2014) - Majer, Jakub; Jurczak, Janusz; Kwiatkowski, Piotr; Cotarca, Livius
Abstract A highly enantioselective hetero‐Diels—Alder reaction of triene (I) and ethyl glyoxylate by using a readily available Ti‐BINOL complex as catalyst is developed.